2020
DOI: 10.12674/ptk.2020.27.1.78
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Barefoot, Kinesio Tape, and Dynamic Tape on Static and Dynamic Balance in Subjects With Asymptomatic Flexible

Abstract: Balance Dynamic tape Flexible flatfoot Kinesio TapeBackground: Flat-footed persons with collapsed medial longitudinal arch lose flexibility after skeletal maturity, resulting in several deformities and soft tissue injuries. Although arch support taping is usually applied in the clinic to support the collapsed arch, research on the use of different types of tape for more efficient arch support in flat-footed persons is lacking. Objects:The purpose of this study was to examine three conditions (barefoot, kinesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
0
9
0
1
Order By: Relevance
“…In addition, it was reported that motor control using tape could be performed in a way that occupies a part of a load of the upper extremity, and that the ability of muscle tissue is improved by positioning the shoulder [21]. According to other previous papers, it has an effect on static and dynamic balance ability [23,24]. As a result of applying dynamic tape on the scapula for shoulder pain, disability, upper body posture, and range of motion in patients undergoing surgery, applying dynamic tape were effective in improving shoulder dysfunction level, range of motion and upper extremity posture for patients who underwent acromioplasty and rotator cuff repair [25].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was reported that motor control using tape could be performed in a way that occupies a part of a load of the upper extremity, and that the ability of muscle tissue is improved by positioning the shoulder [21]. According to other previous papers, it has an effect on static and dynamic balance ability [23,24]. As a result of applying dynamic tape on the scapula for shoulder pain, disability, upper body posture, and range of motion in patients undergoing surgery, applying dynamic tape were effective in improving shoulder dysfunction level, range of motion and upper extremity posture for patients who underwent acromioplasty and rotator cuff repair [25].…”
Section: Discussionmentioning
confidence: 99%
“…Lim& Park, (2020) have investigated the effect of DT application on dynamic balance in adult subjects with flat foot and concluded that DT may be useful to improve dynamic balance (Lim & Park, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…27 This tape possesses unique properties, including four-way stretchability, strong elastic resistance, and recoil; DT can stretch up to at least 200% (unlike KT, which stretches to about 140%) of its original length, with no rigid. 27, 28, 29 By using DT to lift and support the weight of the breast, the occlusion in the lymphatic vessels of the breast is reduced and lymphatic drainage is stimulated; this in turn, helps decrease the perception of pain, promotes blood circulation, and allows faster healing. This study explored the effectiveness of DT as a non-surgical intervention for treating LBAs in postpartum women in India.…”
Section: Introductionmentioning
confidence: 99%